Engaging pragmatics in intercultural communication.: Engaging pragmatics in intercultural communication. - Majidova, Gulruh (Физическое воспитание, спорт и здоровье, 2021)
Abstract: The article aims at giving insights into the significance of pragmatics in maintaining effective intercultural communication. Even though language is the medium of communication it sometimes can not convey the intention of speakers and as a result there may appear misinterpretation of the ideas expressed by words. To avoid such kind of misunderstanding pragmatics comes to help by which conversation may go smoothly.